Multimodalidades e leitura de cartazes de filmes - Leandro, José Israel Pereira (2017)
This TCF presents a movie poster reading practice to classes of Portuguese Language of the last grades of Elementary Teaching. Its contribution stemed from the principle that the reading conception and textual production, nowadays pass for a moment of deep conceptual and methodological changes. Because of this, this proposal seek to understand the text in a multimodal perspective: an heterogeneous element of language that can combine as the verbal language as any other types of language to messages creation. Starting from this plural comprehension of language it is proposed a movie poster reading practice through its compositional resources. Methodologically, for the fact that it is a study about the genre movie poster that materialize it in real situations of use, this research brings a study about the question of multimodality, multiliteracies and the new Technologies of Communication and Information TICs, to use these theories in the locus where they were applied. As principal theoretical reason they will be discussed the conceptions about multimodality and multiliteracies according to Rojo (2012), Dionisio (2005), the conceptions about reading from Kleiman (2013), the conceptions about the Grammar of Visual Design (GVD) from Kress and Van Leeuwen (1996) and many other authors. In addition to these concepts it also discusses the language teaching in a traditional perspective in opposition to a teaching with interaction, understood as a cultural and socio-historical process. Also deepen the discussion about textual genres and how the TICs contribute to the creation and disclosure of them, in this regard, the discussion about the TICs dialogues with the approach done about the relevance that the Learning Objects (LO) offer to the learning of students and teachers. For the fact that it is a work performed for the reading if images, it is done a study of posters of movies that represents the corpus of this work. As theoretical reason, it does the use of the postulancies of the GVD in the words of Magalhaes (2013), Santos (2011), Morais (2011), Almeida (2012) and many others. After all these discussions we have a presentation of a series of activities done in class that seek to check the importance of the concepts presented in this proposal. Who justify this practice is Gil (2002) and Dell’ Isola (2007). As pedagogical proposal for this work we present as product the creation of a pedagogical video (an OA) that condense the concepts worked in this dissertation and presents a proposal of analysis of movie posters to awake in the students the practices of analysis of multimodal texts.